Communication Between Epithelial–Mesenchymal Plasticity and Cancer Stem Cells: New Insights Into Cancer Progression - Zheng, Xiaobo; Dai, Fuzhen; Feng, Lei; Zou, Hong; Feng, Li; Xu, Mingqing (Frontiers in Oncology, 2021)
The epithelial–mesenchymal transition (EMT) is closely associated with the acquisition of aggressive traits by carcinoma cells and is considered responsible for metastasis, relapse, and chemoresistance. Molecular links between the EMT and cancer stem cells (CSCs) have indicated that EMT processes play important roles in expression of CSC-like properties. It is generally thought that EMT-related transcription factors (EMT-TFs) need to be downregulated to confer an epithelial phenotype to mesenchymal cells and increase cell proliferation, thereby promoting metastasis formation. However, the genetic and epigenetic mechanisms that regulate EMT and CSC activation are contradictory. Emerging evidence suggests that EMT need not be a binary model and instead a hybrid epithelial/mesenchymal state. This dynamic process correlates with epithelial–mesenchymal plasticity, which indicates a contradictory role of EMT during cancer progression. Recent studies have linked the epithelial–mesenchymal plasticity and stem cell-like traits, providing new insights into the conflicting relationship between EMT and CSCs. In this review, we examine the current knowledge about the interplay between epithelial–mesenchymal plasticity and CSCs in cancer biology and evaluate the controversies and future perspectives. Understanding the biology of epithelial–mesenchymal plasticity and CSCs, and their implications in therapeutic treatment may provide new opportunities for targeted intervention.